ELECTIONS, THE ETHNIC FACTOR AND PATRONAL POLITICS IN THE RUSSIAN REGIONS anatomy of loyalty. - Shkelʹ, S. N. (ROUTLEDGE, 2025)
This book focuses on the intricacies of elections within Russian ethnic republics and political loyalty in these regions. Many of the ethnic republics support the Russian president and the ruling party to a significantly greater degree than the national average and serve as crucial regional pillars in maintaining the stability of electoral authoritarianism in Russia. Why are non-Russian voters so supportive to the Russian president? How does the ethnic factor contribute to the situation and what are the specific mechanisms involved? Through a comparative analysis of five ethnic republics - Tatarstan, Bashkortostan, Komi, Chuvashia, and Yakutia - the author addresses these questions and uncovers the specific mechanisms of electoral loyalty alongside some erosion of electoral support for the authorities in recent years. This volume will be of interest to readers seeking to improve their understanding of contemporary Russia's political regime, the logics of its sustainability, and potential points of vulnerability, as well as academic scientists and students of modern authoritarianism, ethnopolitics, elections, and Russian politics.
Keywords: Local elections -- Russia (Federation); Russia (Federation) -- Politics and government.; elektronické knihy; electronic books